The Impact of Umbilical Cord Clamping Time on the Infant Anemia: A Randomized Controlled Trial - Sevil Güner; Birsen Karaca Saydam (Tehran University of Medical Sciences, 2021)
Background: Anemia during infancy causes irreversible physical, cognitive, motor, and behavioral development disorders. This study aimed to determine the effect of delaying umbilical cord clamping time on certain parameters regarding anemia during the infancy. Methods: This randomized controlled trial was conducted at a university hospital in west of Turkey (Dec 2017-Dec 2018). Overall, 110 participants were evaluated for the research, 65 participants were randomized after excluding those who did not meet the inclusion criteria (intervention=32, control=33). Randomly assigned to delayed clamping (1 min after delivery) or early clamping (in 15 sec after delivery), and followed up until 4 months postpartum. 48th-hour hematocrit, bilirubin values, need for phototherapy and hematocrit, hemoglobin values, diagnosis of anemia at the postnatal fourth month were compared between two groups. The data showing normal distribution were assessed using the parametric tests. The level of statistical significance was determined as P<0.05. Results: The 48th-hour hematocrit and bilirubin levels of the intervention group were significantly higher than the control (P<0.01 and P<0.05, respectively). No significant difference regarding the need for phototherapy due to postnatal hyperbilirubinemia was observed between the two groups (P>0.05). Means of the intervention group hematocrit and hemoglobin levels measured during anemia screening performed at the fourth month were found to be higher than those of the infants in the control group (P<0.05 and P<0.05, respectively). Conclusion: Delaying umbilical cord clamping had a positive impact on the haematological parameters of infants. Clamping the cord at least one minute in birth can be performed to prevent the iron deficit anemia that could be seen during the first years of infants' lives.